A ESFERA DA COTIDIANIDADE E DA NÃO-COTIDIANIDADE: DESAFIOS E LIMITES NA AÇÃO DO PEDAGOGO NA ESCOLA - Schvarz, Liliani Hermes Cordeiro (2014)
The objective of this research is to analyze some elements regarding the pedagogue`s action in scholar quotidian and no-quotidian. Some efforts were concentrated to understand this phenomenon since Agnes Heller`s Marxist theory and philosophy about daily life. Therefore, quotidian category was the base of this study. About the pedagogue`s formation and his professional performance some texts by Dermeval Saviani, José Carlos Libâneo, Selma Garrido Pimenta, and others, were read. These texts helped to understand the historical phenomenon of Pedagogy in Brazil since its beginning in 1939 until the propositions from National Curricular Policy to Pedagogy graduation in 2006. A field survey was also performed with ten pedagogues from public and private schools where there were Junior High School and High School students in Guarapuava/PR. The semi structured interview was the instrument to collect data. The analysis of the data was based on dialectical historical materialism and Agnes Heller`s theory. Considering limitations of this study, results were people are interested in practice formation whose assumption is that the objective of pedagogue`s formation is the know-how, the savoir-faire. It was also possible to notice the predominance of pedagogue`s action based on common sense to the detriment of theoretical scientific knowledge since the pedagogue`s professional work have been influenced a lot of by daily actions, some of them alienated.